Quality And Efficiency Of Economic Development - Suvaryan, Yu. M.; Manucharyan, Meri G. (ՀՀ ԳԱԱ)
The quality of economic development is expressed by continuous improvement in the spheres of production, consumption and services, which ensures an increase in the quality of life of the population and environmental stability. Quality economic development includes sustainable growth, social justice, technological innovation, and increased access to education and health services. The efficiency of the development is determined by the optimal use of resources, the increase in productivity and the modernization of the structure of the economy. This implies not only an increase in the rate of economic growth, but also an improvement in operational efficiency, competitiveness of organizations and the investment environment. The research presents the main ideas of the quality and efficiency of economic development, presenting the features of development processes aimed not only at quantitative growth, but also at qualitative improvement. The article also discusses the structure of the GDP, the structure of RA foreign trade, including the export and import of high-tech products, emphasizing the role of scientific industrial technologies and knowledge as important factors of the quality of economic development.
Keywords: Economic Development